Ipomoea carnea associated phytochemicals and their in silico investigation towards Meloidogyne incognita. (31st December 2023) - Abdullah, M. M.; Khan, Amir; Albargi, Hasan B.; Ahmad, Mohammad Zaki; Ahmad, Javed; Ahmad, Faheem; Akhtar, Mohammad Shabib; Mohsin, Nehal; Ahmad, Fuzail; Kamal, Mohammad Azhar; Alqurashi, Yaser E.; Lal, Hira; et al.
ABSTRACT: Root-knot nematodes ( Meloidogyne spp.) are sedentary endo-parasite that causes severe yield loss in carrot. Chemical nematicides currently used to manage Meloidogyne incognita are being phased out because of rising health and environmental issues. This study aimed to evaluate nematicidal effect of various concentrations, viz., 250, 500, 750, 1000ppm of leaf extract of Ipomoea carnea against M. incognita infecting carrot under in vitro and in pots assays. In our result, all tested concentrations displayed J2s mortality and egg hatching inhibition along with improving growth of carrot and reduced J2s population and root-knot index. Molecular docking performed predicts binding interactions of two major compounds, viz., neophytadiene and 2-amino-2-methyl-1-propanol as shown by GC-MS analysis with targeted protein, odorant response gene-1 of M. incognita, to confirm nematicidal action of I. carnea leaf extract. The obtained results also suggested that neophytadiene interacted more and strongly bound with odorant response gene-3 than 2-amino-2-methyl-1-propanol. The biochemical ligand-target protein interaction described in the present work will be helpful in the logical selection of biomolecules and essential proteins. Therefore, plant extract may be used the best alternative to chemical nematicides to control root-knot nematodes and caused longitudinal growth of the plant as well as reduce environmental risks.